STRATEGI ADAPATASI NELAYAN PENGEMBANGAN WISATA PANTAI 9 DI DESA BRINGSANG, KECAMATAN GILI GENTING KABUPATEN SUMENEP - Widiyanto Kusumah; Arie Wahyu Prananta Prananta; Aminah Dewi Rahmawati Rahmawati; Syamsu Budiyanti (Journal Social Politica, 2022)
The construction of Pantai 9 Sumenep distric Madura Island has had positive and negative impacts on the Madurese community. Ecotourism project development that has been planned by the government certainly requires a land acquisition program. This land acquisition program became the next stage with the establishment of Pantai 9 to turn Madura into an industrialized area. The pros and cons of the people of Pantai 9 in the land acquisition program have made the community fight against the government. To find out the form of community resistance to the government in land acquisition for ecotourism projects in Bringsang Village, Gili Genting District, Sumenep Regency. purposive sampling technique, the type of data used is primary data and secondary data. Primary data obtained from unstructured interviews. Secondary data obtained from literature study. In this study to analyze the data using the theory of resistance Sidney Tarrow. The results showed that the form of resistance owned by the people of Pantai 9 was with actions based on the politics of resistance that facilitated the public to openly express opinions. Creating an organizational structure for community groups against evictions as a vehicle for mobilizing the resistance movement and the process of framing the Pantai 9 community groups together making banners by creating meanings by displaying slogans.